The European Central Bank's quantitative easing programme: Limits and risks - Grégory Claeys; Álvaro Leandro (Bruegel, 2016)
[Highlights] The European Central Bank (ECB) has made a number of significant changes to the original guidelines of its quantitative easing (QE) programme since the programme started in January 2015. These changes are welcome because the original guidelines would have rapidly constrained the programme's implementation. The changes announced expand the universe of purchasable assets and give some flexibility to the ECB in the execution of its programme. However, this might not be enough to sustain QE throughout 2017, or if the ECB wishes to increase the monthly amount of purchases in order to provide the necessary monetary stimulus to the euro area to bring inflation back to 2 percent. To increase the programme's flexibility, the ECB could further alter the composition of its purchases. The extension of the QE programme also raises some legitimate questions about its potential adverse consequences. However, the benefits of this policy still outweigh its possible negative implications for financial stability or for inequality. The fear that the ECB's credibility will be undermined because of its QE programme also seems to be largely unfounded. On the contrary, the primary risk to the ECB's credibility is the risk of not reaching its 2 percent inflation target, which could lead to expectations becoming disanchored.
Keywords: 330